2023
DOI: 10.21203/rs.3.rs-2879768/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

O. volvulus microfilariae in the anterior chambers of the eye and ocular adverse events after a single dose of 8 mg moxidectin or 150 µg/kg ivermectin: Results of a randomized double-blind Phase 3 trial in the Democratic Republic of the Congo, Ghana and Liberia

Abstract: Background After ivermectin became available, diethylcarbamazine (DEC) use was discontinued because of severe adverse reactions, including ocular reactions, in individuals with high O. volvulus microfilaridermia. Assuming long-term ivermectin use led to < 5 microfilariae/mg skin (SmfD) with little or no eye involvement, DEC + ivermectin + albendazole treatment a few months after ivermectin was proposed. In 2018, the US FDA approved moxidectin for treatment of O. volvulus infection. The Phase 3 study evaluat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 62 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…In vitro studies suggest that ivermectin acts by inhibiting the host importin alpha/beta-1 nuclear transport proteins, which are part of an intracellular transport process that viruses hijack to enhance infection by suppressing the host's antiviral response, underlying its use against viruses such as dengue virus, yellow fever virus, and Zika virus. Studies have also suggested anti-inflammatory properties, which have been hypothesized to be beneficial in SARS-CoV2 infections [ 3 , 4 , 5 , 6 ]. Despite these studies, no clinical trials have reported a clinical benefit of ivermectin against all these viral infections.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro studies suggest that ivermectin acts by inhibiting the host importin alpha/beta-1 nuclear transport proteins, which are part of an intracellular transport process that viruses hijack to enhance infection by suppressing the host's antiviral response, underlying its use against viruses such as dengue virus, yellow fever virus, and Zika virus. Studies have also suggested anti-inflammatory properties, which have been hypothesized to be beneficial in SARS-CoV2 infections [ 3 , 4 , 5 , 6 ]. Despite these studies, no clinical trials have reported a clinical benefit of ivermectin against all these viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…At therapeutic doses, ivermectin does not readily penetrate the blood-brain barrier, where GABA functions as a neurotransmitter. The therapeutic dosage recommended is 0.2-0.3mg/kg/day, with a maximum daily dosage of 0.4mg/kg/day [ 3 , 4 ]. Ivermectin has a high margin of safety in humans and does not readily cause serious adverse drug reactions since it is transported out of the central nervous system by ATP-binding cassette subfamily B member 1 (ABCB1) transporter [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations